Simbiosis Idola dan Penggemar: Dinamika Resiprositas Economic Means dan Symbolic Means dalam Fandom Arashi - Firtha Ayu Rachmasari (Universitas Airlangga, 2026)
The relationship between idols and fans in contemporary popular culture is no longer understood as a one-way process of consumption, but as an ecosystem sustained by the exchanges of both material and symbolic value. This study aims to examine the dynamics of reciprocity between the idol group Arashi and its fans by analyzing how fans provide support through economic means, whereas Arashi reciprocates through symbolic means. This study is a descriptive qualitative study using a literature-based research method. The data were analyzed through thematic analysis of relevant literature, documents, and publications. The findings show that the symbolic means Arashi distributes through intensive fan service play a crucial role in fostering strong emotional bonds and deep fan loyalty. This affective loyalty generates collective responses in the form of economic support, as fans consciously allocate financial resources to purchase goods, albums, and concert tickets to sustain the group's activities and presence. The study concludes that the relationship between Arashi and its fans constitutes a mutualistic symbiosis driven by an affective economy, in which symbolic capital and economic capital are continuously exchanged to maintain the sustainability of the fandom ecosystem.